Quantifying phosphine penetration through the bark of pine (Pinus radiata D.Don) logs. (September 2018) - Hall, Matthew; Pal, Pranoy; Pranamornkith, Thamarath; Adlam, Anthony; Najar-Rodriguez, Adriana; Hall, Alistair; Brash, Don
Abstract: Phosphine (PH3 ) is used as an in-transit phytosanitary treatment (10-d fumigation period) for pine ( Pinus radiata D.Don) logs exported from New Zealand to China. The ability of PH3 to penetrate through the bark of the logs is not well known. We designed equipment to accurately quantify PH3 penetration into the bark of wooden blocks (100 × 100 × 50 mm; n  = 12) cut from the upper and lower trunk of recently harvested pine trees fumigated at 15 or 25 °C. Fumigations simulated commercial conditions consisting of two phases; phase I with 2.0 g m −3 of PH3 for the first 5 days (1–120 h) and 1.5 g m −3 of PH3 in phase II for the next 5 days (121–240 h). During the 10-d schedule, we achieved the required commercial CT (concentration × time) of ≥48, 000 ppm h at both temperatures. Bark thickness (i.e., trunk location) did not significantly affect fumigant penetration. Phosphine penetration through the bark of the wooden blocks was greatest after each application, then the penetrated concentrations diminished over time. Greater penetration occurred at 15 °C than at 25 °C. Further studies are required to better understand the dynamics of PH3 penetration particularly at lower temperatures and through insect-infested blocks. Highlights: The ability of phosphine to penetrate through the bark of pine logs is not well known. We quantified PH3 penetration into the bark of wooden blocks fumigated at 15 or 25 °C. Bark thickness did not affect fumigant penetration as opposed to temperature. Fumigant dynamics followed Equilibrium law with 3x greater penetration occurring at 15 °C.